2011
DOI: 10.1111/j.1365-2141.2011.08832.x
|View full text |Cite
|
Sign up to set email alerts
|

MYH9 and APOL1 are both associated with sickle cell disease nephropathy

Abstract: SUMMARY Background Renal failure occurs in 5–18% of sickle cell disease (SCD) patients and is associated with early mortality. At risk SCD patients cannot be identified prior to the appearance of proteinuria and the pathobiology is not well understood. The MYH9 and APOL1 genes have been associated with risk for focal segmental glomerulosclerosis and end-stage renal disease in African Americans. Methods We genotyped 26 SNPs in MYH9 and 2 SNPs in APOL1 in 521 unrelated adult (18–83 years) SCD patients screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 43 publications
3
112
0
Order By: Relevance
“…One setting in which the adaptive processes drive APOL1 FSGS is perhaps the report that APOL1 variants are associated with proteinuric sickle cell nephropathy (97), although a systematic study of kidney histology in APOL1-associated sickle nephropathy is still lacking. APOL1 high-risk alleles are strongly associated with collapsing glomerulopathy in several settings: (1) HIVAN, in which 72% have two APOL1 high-risk alleles (83), and (2) the use of exogenous IFN (98) and in lupus (99).…”
Section: Emerging Pathologic Mechanisms: Apol1-associated Fsgsmentioning
confidence: 99%
“…One setting in which the adaptive processes drive APOL1 FSGS is perhaps the report that APOL1 variants are associated with proteinuric sickle cell nephropathy (97), although a systematic study of kidney histology in APOL1-associated sickle nephropathy is still lacking. APOL1 high-risk alleles are strongly associated with collapsing glomerulopathy in several settings: (1) HIVAN, in which 72% have two APOL1 high-risk alleles (83), and (2) the use of exogenous IFN (98) and in lupus (99).…”
Section: Emerging Pathologic Mechanisms: Apol1-associated Fsgsmentioning
confidence: 99%
“…16 The second found that individuals with the APOL1 G1/G2 risk variants (defined as being homozygous or compound heterozygous for the G1 and/or G2 risk variants using a recessive model) were 3.4-times more likely to have dipstick-defined proteinuria and that variants in MYH9 were independently associated with proteinuria after adjusting for APOL1 variant status. 17 Furthermore, a significant interaction between the APOL1 G1/G2 risk variants and an MYH9 risk haplotype was observed in predicting eGFR.…”
Section: Introductionmentioning
confidence: 93%
“…Variants in BMPR1B (rs2240036, rs4145993, rs17022863, rs1434549, rs1470409, rs4331783) and MYH9 (rs5756129, rs11912763, rs16996648, rs5750248, rs1557529, rs5756152, rs8141189, rs1005570. rs16996672, rs933224) that had been previously identified in the literature as being associated with sickle cell nephropathy 16,17 were also examined for associations with eGFR and urine albumin concentrations, respectively. The imputation qualities for BMPRIB and MYH9 are provided in Online Supplementary Table S1. HMOX1 and SOD2 were candidate genes identified as having differential expression from the PCR experiments.…”
Section: Genotyping In the Uic And Walk-phasst Cohortsmentioning
confidence: 99%
“…This scenario is proposed for renal disease associated with sickle cell disease, with collapsing nephropathy associated with lupus or HIV and with compromised graft survival after transplantation. [4][5][6][7][8][9] APOL1 risk variants are associated with earlier age of onset and progression to renal failure of subjects with FSGS, and prospective studies in the African American Study of Kidney Disease and Chronic Renal Insufficiency cohorts show that carriage of two APOL1 risk variants is associated with more rapid progression to clinical endpoints in persons with renal insufficiency at study entry. 2,3,5,7,8 Moreover, African-American participants without renal disease on enrolment in the ARIC study were more likely to develop CKD and to progress to renal failure if they had two APOL1 risk alleles, compared with those with no alleles or one allele.…”
Section: The Similarity Of Thementioning
confidence: 99%